Pengaruh Pendapatan Sektor Perikanan dan Pertanian Terhadap Perekonomian Daerah Kabupaten Lampung Timur Tahun 2018-2022 - Aulia, Nabila (Universitas Negeri Surabaya, 2023)
The fisheries and agriculture sector in East Lampung District is the sector that received investment funds of 48.25%, which is greater than the industrial sector at 17.15%. In addition, the fisheries sector is a sector that has the top five revenues in the economy of the Lampung province region. This study aims to analyze the effect of fisheries and agriculture sector income on the regional economy of East Lampung District in 2018-2022. The type of research used is quantitative research with the analysis technique used, namely multiple linear regression analysis using SPSS version 20. The results of the analysis show that the fisheries and agriculture sectors have an effect on the regional economy. Therefore, all hypotheses in this study are accepted.